Exploring English Language Teaching in an Ecuadorian Urban Secondary Institution (GIST – Education and Learning Research Journal, 2017)
This article presents a case study focused on the pedagogy of nine English language teachers’ pedagogy in Ecuador. The significance of this study is its potential to inform practitioners, teacher educators, and policymakers in countries where teachers need to be prepared to teach in multilingual settings, such as Ecuador. Data analyses of nine observations of practicing teachers seems to suggest the curriculum used to prepare English teachers does not fully meet the educational needs of teachers or students. Observations of secondary level English teachers were conducted using the Classroom Observation Checklist (2010). This instrument is useful to analyze teachers’ delivery of content, lesson organization, classroom interactions, verbal and non-verbal communication in the classroom, and integration of media during instruction. One major theme emerged from data analyses; English language teaching appears to follow teaching as a foreign language paradigm. The validation of the results of this exploratory study through the participation of a larger sample size of classroom teachers would be important to provide a more robust conclusion regarding teaching diverse student populations.
Keywords: Teacher Preparation; Multilingual Students; Multilingual Educational Context; English Language Teaching